The Effects of Atmospheric Processes on Tehran Smog Forming - H Mohammadi; D Cohen; M Babazadeh; L Rokni (Tehran University of Medical Sciences, 2012)
Air pollution is one of the most important problems in urban areas that always threaten citizen's health. Photochemical smog is one of the main factors of air pollution in large cities like Tehran. Usually smog is not only a part of nature, but is being analyzed as an independent matter, which highly affects on the nature. It has been used as relationship between atmospheric elements such as temperature, pressure, relative humidity, wind speed with inversion in the time of smog forming and weather map in 500 Hpa level during 9 years descriptive static by using correlation coefficient in this analyze.  Results show that there is a meaningful correlation between atmospheric elements and smog forming. This relation is seen between monthly average of these elements and monthly average of smog forming. However, when temperature decreases, corresponding pressure will increase and result of this will be smog forming. Usually smog increases in cold months of year due to enter cold high pressure air masses in Iran during December and January that is simultaneous with decreasing temperature and air pressure increases and inversion height distance decreases from the earth surface which cause to integrate air pollution under its surface, will cause to form smog in Tehran. It shows a meaningful and strong relation, based on resultant relations by correlation coefficient from inversion height and smog forming, so that obtained figure is more than 60% .